Implementation of the STEM-Based Project-Based Learning (PjBL) Model to Enhance Students’ Critical Thinking and Creativity in Fusion Food Materials - Setyobudi, Adhi; Sofyan, Herminarto; Komariah, Kokom (Indonesian Journal of Educational Research and Technology, 2026)
This study aims to determine the effect of the STEM-based PJBL learning model on students' critical thinking skills and creativity. This study is a quasi-experimental study with quantitative methods. The study design uses a nonequivalent control group design. The population in this study were 108 students of class XII Culinary Arts at SMK N 1 Bawen in the 2024/2025 academic year. The sampling technique used was proportionate random sampling, obtaining 72 students. Data collection used tests, observations, and questionnaires. The data analysis technique used the MANOVA test. The results of the study show that: (1) there is an effect of the PJBL learning model with STEM on students' critical thinking skills, (2) there is an effect of the PJBL learning model with STEM on students' creativity, (3) there is a difference in critical thinking skills between students taught with PJBL learning with STEM and students taught with conventional PJBL learning, and (4) there is a difference in student creativity towards conventional learning models and PJBL-STEM.